On‐Demand Laser Printing of Picoliter‐Sized, Highly Viscous, Adhesive Fluids: Beyond Inkjet Limitations. Issue 18 (15th July 2018) - Makrygianni, Marina; Milionis, Athanasios; Kryou, Christina; Trantakis, Ioannis; Poulikakos, Dimos; Zergioti, Ioanna
Abstract: Novel printing methods represent a class of emerging technologies, with applications ranging from biomedical to energy devices, attracting significant attention because of their ability to handle new classes of materials. Typically, popular printing technologies, such as inkjet printing, deposit low‐viscosity inks (1–15 mPa s). In a broad range of emerging applications, alternative printing techniques will enable the handling of materials with much higher viscosities. Here, Laser‐induced forward transfer (LIFT) is employed as a direct, nozzleless printing method, enabling the processing of fluids with viscosities far beyond the inkjet printing regime. Specifically, exploiting the capability of LIFT being a high‐speed processing technique, maintaining at the same time high printing resolution, the printing of highly viscous cyanoacrylate adhesives (from 30 to 1700 mPa s) is demonstrated achieving printing resolution down to 30 µm. The volume of the LIFT‐ejected adhesive droplets lies in the picoliter scale. As a further advantage compared with inkjet techniques, the printing resolution can be tuned on demand by adjusting the laser fluence during the process. Finally, as an application example, the attachment of chemical indicator powders (i.e., dimethylglyoxime powder) on printed adhesives patterns is illustrated, creating heavy metal sensors with remarkable fabrication facility. Abstract : Laser‐induced forward transfer is employed as a direct, nozzleless printing method enabling the processing of fluids with viscosities greater than the inkjet limitations. Printing of highly viscous adhesives (up to 1700 mPa s) is achieved with high printing resolution of picoliter‐sized adhesive droplets. In addition, chemical microsensor arrays are fabricated on plastic substrates with remarkable fabrication facility.